Introdução dos princípios da filosofia de construção enxuta no processo de produção em uma construtora em Passo Fundo-RS - Kurek, Juliana (2005)
For many decades, the construction industry has been developed based on a production management model which emphasizes conversion activities, i.e. the processing or modification in the shape or substance of the materials. This model clearly neglects all the flow activities involved in the production process, such as inspection, transport, and delay time. In the last few years, however, general efforts are being made aiming at the construction industry modernization and the implementation of a production model that considers both conversion and flow. This new approach, which was been generally called Lean Production or Lean Construction, is the result of a great deal of research work done mainly by the academic community with the cooperation of governmental and industrial institutions as well as of individual construction companies. In this context, the main objective of the present work is to introduce the basic principles of Lean Production in a construction company in the city of Passo Fundo/RS, taking into account the regional reality and the actual possibilities of intervention in the company production processes. The case study described herein was divided into three different phases. At first, an exploratory study was carried out to get basic information and set a benchmark for the analysis, which included the identification of the company, the full description of the production processes, and the direst site observation of working people. In the second phase, the principles of lean construction were presented to the company staff and the interventions in the production processes were planned and implemented. In the last phase, from the evaluation and discussion of the results, a checklist for the diagnosis and implementation of basic Lean Production principles in similar construction companies was proposed. Amongst the main conclusions drawn from the case study, it can be highlighted taht management tools, as the planning and production control, and the 5S program, along with the integration of the Lean Construction principles to the Brazilian Program of Habitat Quality and Productivity (PBQP-H), provide a new standard that makes possible major improvements in the construction industry. Also, the study showed the necessity of extending the work done to other construction companies in the Passo Fundo region, so the principles of Lean Construction could be widely discussed, learned, and practiced